Monetary economics after the global financial crisis: what has happened to the endogenous money theory? - Giuseppe Fontana; Riccardo Realfonzo; Marco Veronese Passarella (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2020)
The 2010s have witnessed a new shift in central banking and, partially at least, in monetary economics and macroeconomic modelling. It is a fact that the endogenous money theory has been gradually clawing back popularity at the expense of the classical theory of interest rates, the financial intermediation view of banks, the money-multiplier story and the quantity theory of money. However, the loanable funds theory and the view of banks as pure financial intermediaries (sometimes coupled with the money-multiplier story) are still sometimes invoked. In addition, the dynamic process of creation, circulation and destruction of money is usually neglected. The point is that money endogeneity is still regarded by many mainstream economists as a mere empirical fact, not a key feature of capitalist market-based economies to be properly explained by a logically consistent theory. By contrast, dissenting economists have further advanced the endogenous money view through: (a) a generalised theory of the endogenous process of money creation; (b) the increasing popularity of modern monetary theory in the public debate; and (c) the development of aggregative stock–flow consistent models and agent-based stock–flow consistent models as an alternative to dynamic stochastic general equilibrium models.
Keywords: B52; E12; E51; E52; 330; endogenous money; exogenous money; quantitative easing; inflation targeting; modern monetary theory; stock–flow consistent models